Geology of the polyphase Olympica – Jovis Fossae channel system - Anita Zambrowska; Daniel Mège; Sam Poppe (Journal of Maps)
Outflow channels of the Tharsis province on Mars testify to the drainage of groundwater reservoirs through magmatic and tectonic processes. The Olympica – Jovis Fossae system extends over 500 km, but the significance of its deep and narrow channels for the Tharsis dome is poorly understood. We present a new geologic map of Olympica-Jovis Fossae where we mapped landforms and geological units, dated them relatively, and identified the chronological succession of outflow events and deposition of lava flows, airfall, and sedimentary units. Cross-cutting relationships indicate a complex succession of 28 channel incisions in the volcanic stratigraphy. The five identified morphological channel types indicate different flow dynamics at different times and places. The map highlights the role of intensive volcanic activity in releasing water from overpressurized aquifers and possible subglacial flows, and will assist in a better understanding of the general conditions for catastrophic groundwater flooding in a volcanic context.